Feminism and Finitude - Alessandra Mularoni (Technophany, 2023)
This essay examines the ideological parallels between the transhuman pursuit for immortality and xenofeminism’s call for biological manipulation. Paying particular attention to the patriarchal legacy of technoscience, I identify eugenic principles embedded in the discursive emphasis on anti-naturalism, freedom, and alienation. My intention is to recuperate xenofeminism’s more radical manoeuvres by resituating its aims through a historical materialist approach. Specifically, I suggest a reinterpretation of nature as inherently technological. In so doing, I argue for an alliance between xenofeminism and ecofeminist political economy to engage a discursive redirection toward degrowth and dealienation. I then build on Rosi Braidotti’s (2013) posthuman theory of death to suggest an uncomfortable biopolitical expansion: a biopolitics for the Anthropocene should not only seek an equal right to live, but also an equal predisposition to death. My countervailing materialism centres a politics of finitude through an analysis of the vital-fatal entanglement in the body’s reproductive capacities.